On the development of the brown spider Loxosceles gaucho Gertsch (Araneae, Sicariidae): the nympho-imaginal period - Rinaldi, Isabela M.P [UNESP]; Forti, Luiz Carlos [UNESP]; Stropa, André A [UNESP] (Sociedade Brasileira de Zoologia, 1997)
Observations of the developmental biology of Loxosceles gaucho Gertsch, 1967, the brown spider of southeastern Brazil are scarce. The present study reports the method of individualized rearing of 18 populations of L. gaucho, kept in laboratory under varied diet conditions, and characterizes their nympho-imaginal period as well as factors related to their reproduction. Females built the first egg sac about 20 days after copulation and nymphs hatched 40 days after the laying date. Average offspring was 61.3 spiderlings and females usually built three to four successive egg sacs in a period of five to seven months. First nymphs initiated their predatory activity between the 5th and 8th days after hatching and the majority reached adulthood within six moults (range of five to eight) in approximately 15 to 17 months (male) and 15.5 to 18 months (female). The average sex ratio equaled 1.0:1.7 (male:female). The wide individual variability of this species intermoult intervals is herewith expressed by the intermoult rate, which was fairly uniform for both intra and interpopulations and gives a relevant aspect for a general idea of the life cycles of spiders.
Keywords: Brown spider; Loxosceles gaucho; Sicariidae; development